2020
DOI: 10.3390/molecules25040992
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Enhances the Antibacterial Activity of Honey against Planktonic and Biofilm-Embedded Bacteria

Abstract: Multifactorial antibacterial action is an important feature of honey; however, its bactericidal efficacy against biofilm-embedded bacteria is limited. The aim of this study was to investigate the impact of vitamin C (Vit C) on the antibacterial activity of natural honeys against planktonic as well as biofilm-embedded bacterial pathogens. The antibacterial activity of four honey samples supplemented with Vit C was expressed as the minimum inhibitory concentration (MIC). At sub-MICs, Vit C significantly increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 40 publications
3
35
0
Order By: Relevance
“…Numerous studies have shown that vitamins C and E exert antimicrobial activity against a wide range of microorganisms, including Staphylococcal species (including Staphylococcus aureus), Streptococcal species, Proteus vulgaris, Escherichia coli, Bacillus subtilis, Candida albicans, Pseudomonas aeruginosa, and Klebsiella pneumoniae [50][51][52][53]. In addition, these vitamins can have synergistic effects with antibiotics and enhance growth inhibition and the lethal effects of antibiotics against microorganisms [40,50,[54][55][56][57][58][59][60][61][62][63]. Recent studies emphasize that vitamins C and E can also enhance the antimicrobial activity of honey [24,37,38,50].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous studies have shown that vitamins C and E exert antimicrobial activity against a wide range of microorganisms, including Staphylococcal species (including Staphylococcus aureus), Streptococcal species, Proteus vulgaris, Escherichia coli, Bacillus subtilis, Candida albicans, Pseudomonas aeruginosa, and Klebsiella pneumoniae [50][51][52][53]. In addition, these vitamins can have synergistic effects with antibiotics and enhance growth inhibition and the lethal effects of antibiotics against microorganisms [40,50,[54][55][56][57][58][59][60][61][62][63]. Recent studies emphasize that vitamins C and E can also enhance the antimicrobial activity of honey [24,37,38,50].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these vitamins can have synergistic effects with antibiotics and enhance growth inhibition and the lethal effects of antibiotics against microorganisms [40,50,[54][55][56][57][58][59][60][61][62][63]. Recent studies emphasize that vitamins C and E can also enhance the antimicrobial activity of honey [24,37,38,50].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations